TRENDS IN THE DEVELOPMENT OF PEACEFUL MEANS FOR INTERNATIONAL DISPUTE RESOLUTION IN THE CONTEXT OF INTERNATIONAL CONSTRUCTION CONTRACT LAW - BELKIN Dmitry Semenovich (Правовое государство: теория и практика, 2025)
In the framework of international construction contract law at the present stage, the pursuit for effective and peaceful dispute resolution methods remains a critical factor. Their relevance is determined by the growth of transnational projects and the necessity for unified approaches to conflict settlement. This study aims to identify the principal trends and directions in the development of peaceful means for resolving international construction disputes, taking into account the rising number of crossborder contracts and the increasing activity of international judicial institutions. The analysis is based on the comparative legal method, content analysis of scholarly publications and international conference materials, and a review of the practice of international arbitration tribunals. Special emphasis is placed on documents from the International Federation of Consulting Engineers, which regulate arbitration procedures. Results: the findings highlight the relevance of harmonized arbitration and mediation procedures in construction projects, allowing for reduced time and costs in conflict resolution. The study shows that global trends in the operations of international judicial bodies affect national legal frameworks and shape new approaches to the regulation of construction disputes. The study also demonstrates the autonomism of international courts and their interaction with states, influencing the balance between sovereignty and the obligations of participating countries.